1989
DOI: 10.1111/j.1471-0528.1989.tb03280.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic findings in 1250 chorionic villus samples obtained in the first trimester with clinical follow‐up of the first 1000 pregnancies

Abstract: Summary. First‐trimester chorionic villus sampling (CVS) was performed in a series of 1250 pregnancies. The direct method of karyotyping was successful in 1205 (96.4%). Abnormal laboratory findings resulted in 60 terminations of pregnancy (4.8%). In addition, six unexpected balanced chromosome rearrangements were detected. False‐positive cytogenetic findings occurred in 2.3%, comprising 22 with mosaicism confined to the trophoblast, and a further six non‐mosaic false‐positive discrepancies were detected, four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 6 publications
(3 reference statements)
2
13
0
Order By: Relevance
“…For invasive prenatal diagnosis, quanti®ed data are scarce on this topic (Leschot et al, 1989;Chueh et al, 1995). Our study substantiates that operator and centre experience in invasive prenatal diagnosis in¯uence the safety and success of CVS.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…For invasive prenatal diagnosis, quanti®ed data are scarce on this topic (Leschot et al, 1989;Chueh et al, 1995). Our study substantiates that operator and centre experience in invasive prenatal diagnosis in¯uence the safety and success of CVS.…”
Section: Discussionsupporting
confidence: 84%
“…Procedure related fetal loss shows considerable variation. This is usually ascribed to a difference in operator experience (Leschot et al, 1989;Canadian Collaborative CVS±Amniocentesis Clinical Trial Group, 1989; MRC Working Party on the Evaluation of Chorion Villus Sampling, 1991; Brambati et al, 1991Brambati et al, , 1998Lilford, 1991;SmidtJensen et al, 1992;Boehm et al, 1993;Stranc et al, 1997).…”
Section: Introductionmentioning
confidence: 97%
“…Incidence of chromosome abnormalities at CVS in advanced maternal age women. For the autosomal trisomies, sex‐chromosome abnormalities, structural abnormalities and triploidy, the data is based on 16,855 CVS in women aged 35 or older with testing prior to the widespread use of chromosome microarrays . Because these studies may have used various criteria for defining mosaic cases, the results for mosaic other autosomal trisomies was extracted from a separate study involving 45,867 cases.…”
Section: Additional Abnormalities Potentially Detectablementioning
confidence: 99%
“…Although these gestational ages were not identical to those given in some other studies (such as Snijders et al, 1995), a sensitivity analysis showed that the results were robust to small changes in the maternal age adjustment. Macintosh et al (1995) pool maternal agespecific rates of Down syndrome at CVS obtained from the Danish cytogenetic register with CVS data from Snijders et al (1994) and three other published studies (Hook et al, 1988;Leschot et al, 1989;Kratzer et al, 1992). The pooled rates were checked and corrected from the original sources and combined by adding cases and the total number of women undergoing karyotyping at each maternal age.…”
Section: Re-analysismentioning
confidence: 99%